The relationship between the interictal epileptiform discharge source connectivity and cortical structural couplings in temporal lobe epilepsy - Li, Zhensheng; Jiang, Che; Gao, Quwen; Xiang, Wei; Qi, Zijuan; Peng, Kairun; Lin, Jian; Wang, Wei; Deng, Bingmei; Wang, Weimin (Frontiers in Neurology, 2023)
OBJECTIVE: To explore the relation between interictal epileptiform discharges (IEDs) source connectivity and cortical structural couplings (SCs) in temporal lobe epilepsy (TLE). METHODS: High-resolution 3D-MRI and 32-sensors EEG data from 59 TLE patients were collected. Principal component analysis was performed on the morphological data on MRI to obtain the cortical SCs. IEDs were labeled from EEG data and averaged. The standard Low-Resolution Electromagnetic Tomography analysis was performed to locate the source of the average IEDs. Phase locked value was used to evaluate the IEDs source connectivity. Finally, correlation analysis was used to compare the IEDs source connectivity and the Cortical SCs. RESULTS: The features of the cortical morphology in left and right TLE were similar across 4 cortical SCs, which could be mainly described as the default mode network, limbic regions, connections bilateral medial temporal, and connections through the ipsilateral insula. The IEDs source connectivity at the regions of interest was negatively correlated with the corresponding cortical SCs. SIGNIFICANCE: The cortical SCs were confirmed to be negatively related to IEDs source connectivity in patients with TLE as detected with MRI and EEG coregistered data. These findings suggest the important role of intervening IEDs in treating TLE.